2001
DOI: 10.1097/00007890-200108150-00037
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity for the Factor v Leiden (G1691a) Mutation Predisposes Renal Transplant Recipients to Thrombotic Complications and Graft Loss1

Abstract: Heterozygosity for the FVL mutation predisposes renal allograft recipients to venous thromboembolic complications, graft perfusion defects, and early transplant loss. Screening for the FVL mutation and appropriate peri- and postoperative anticoagulation after renal transplantation might prevent these thromboembolic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 8 publications
0
39
1
4
Order By: Relevance
“…Other explanations from previous reports point to the increased risk of renal transplant loss due to perfusion defects in the initial ischemia-reperfusion phase (11).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other explanations from previous reports point to the increased risk of renal transplant loss due to perfusion defects in the initial ischemia-reperfusion phase (11).…”
Section: Discussionmentioning
confidence: 97%
“…As major reasons the occurrence of acute rejections, probably mostly vascular rejections, has been described (6,8,10). Furthermore, rates of early graft loss due to venous thromboembolism and graft perfusion defects were significantly elevated in patient groups tainted with thrombophilia (11). Other groups have recently observed that the prothrombin (PT) G20210A mutation similarly predisposed to early transplant failure (12).…”
mentioning
confidence: 99%
“…6 Studies have shown that recipients with hypercoagulable disorders have a significantly higher risk of early graft failure apart from thromboembolic events and acute rejection. 16 Long-term graft survival is higher when anticoagulants are administered prophylactically. 17 Genetic analysis has shown that single nucleotide polymorphisms seem to have no statistically significant association with acute rejections, except from factor V mutation Q506.…”
Section: Discussionmentioning
confidence: 99%
“…1 A prevalência da mutação FV G1691A na população de receptores renais equivale à da população não transplantada, com pequenas variações de acordo com o grupo étnico estudado. 4,[23][24][25] No presente estudo, a prevalência desta mutação foi de 1,5%, o que é equivalente à observada na população brasileira de não transplantados. 28 Após o transplante renal, existe significativo declínio da atividade fibrinolítica 29 e da ativação da proteína C, 30 além de ativação de trombina, plaquetas e da via intrínseca da coagulação quando os pacientes estão imunossuprimidos com ciclosporina.…”
Section: Discussionunclassified
“…2,3 O número de condições associadas à trombofilia aumentou proporcionalmente ao desenvolvimento de novas metodologias que permitiram a identificação de maior número de polimorfismos em genes relacionados com o sistema de coagulação e de anticoagulação. A mutação G1691A no gene do fator V (FV) do sistema de coagulação (Fator V de Leiden), 4 a mutação G20210A no gene da protrombina (PT) 5 e a presença de anticorpos anticardiolipina (aCL) 6,7 circulantes no sangue periférico são importantes condições associadas à trombofilia e podem influenciar o risco de perda do enxerto renal atribuída a eventos trombóticos. Estudos populacionais indicam, entretanto, que a prevalência de trombofilia não é uniforme.…”
Section: Introductionunclassified